DECISION MAKING PROCESS NUMBER OF CIVIL SERVANT CANDIDATE FORMATIONS AT THE MINISTRY OF LAW AND HUMAN RIGHTS - Rizki Insani; Arief B Suharko (Jurnal Scientia, 2023)
This study aims to determine the best decision in determining the number of formations for Candidates for Civil Servants within the Ministry of Law and Human Rights of the Republic of Indonesia. Data and information were taken from direct interviews with several sources within the Ministry of Law and Human Rights of the Republic of Indonesia who have an important role in determining the policy. The model or method used in conducting this research is Multi Criteria Decision Making with the Analytic Hierarchy Process (AHP) concept. With the calculation of this model formulation, the results of references from the decisions to be selected are obtained, which are then aggregated to obtain results from several sources using the Aggregating Individual Priorities (AIP) method. From the results of the study, shows that the decision in determining the number of formation needs for Candidates for Civil Servants within the Ministry of Law and Human Rights of the Republic of Indonesia is using the Trend or Baseline method.